Rat Liver Function Induced By A High-Fat Diet After Giving Mahogany Seeds Ethanol Extract - Agave Chintya Gabriella Sijabat; Sri Isdadiyanto; Agung Janika Sitasiwi (Biosaintifika: Journal of Biology & Biology Education, 2023)
Intake of a high-fat diet can cause hyperlipidemia which increases the rate of triglycerides and cholesterol, and decrease the HDL levels. The increase of lipid levels in the blood can cause Non-Alcoholic Fatty Liver Disease (NAFLD) which triggers damage of liver function. Mahogany seeds have bioactive compounds that have the potential to be antioxidants in treating hyperlipidemia. This study aimed to analyze the liver function of rats by inducing a high-fat diet after giving mahogany seeds ethanol extract which was observed through the levels of SGOT and SGPT. Thirty male rats of the Sprague Dawley strain were divided into 6 groups of treatment, that were: P0 (only given commercial feed), P1 (given a high-fat diet), P2 (given a high-fat diet and simvastatin at a dose of 8 mg/200 g BW), P3, P4, and P5 (given a high-fat diet and mahogany seeds ethanol extract of 14, 28, and 56 mg/200gBW). The results showed that there was no significant difference between all treatment groups. Administration of mahogany seeds ethanol extract was able to prevent the increase of SGOT and SGPT levels. Mahogany seeds ethanol extract has the hepatoprotective effect against high-fat diet induced hepatotoxicity, thereby affirming its traditional therapeutic role in liver injury.